DEVELOPMENT OF E-BOOKS INTEGRATED WITH HABIST OF MIND AND ISLAMIC CHARACTERS IN IMPROVING ALGEBRAIC THINKING SKILLS OF PROSPECTIVE ELEMENTARY SCHOOL TEACHERS - Wilujeng, Hestu; Aristiawan, Aristiawan (FKIP Universitas Muhammadiyah Tangerang, 2024)
Algebraic thinking skills are important for students because algebraic thinking will promote ways to interpret mathematics. The results of preliminary research on the algebraic thinking ability of PGMI students showed an average problem solving of 18.46, mathematical modelling of 18.26, reasoning ability of 5.54, analytical thinking of 8.8 and generalization of 17, with a maximum value of 20. These results indicate that for indicators of analytical thinking and reasoning students are still low. This study aims to develop an e-book of algebraic thinking skills integrated with habits of mind and Islamic characters for prospective elementary school teachers. This type of research is development research using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The developed e-book was validated by several experts including media experts, material experts and Islamic experts to ensure the quality of the e-book produced before the field trial. Product trials were conducted on 230 PGMI students. Based on the results of the study, it is known that the feasibility of the algebraic thinking ability e-book integrated with habits of mind and Islamic characters is categorized as very good, with a value of 4.77 from a maximum scale of 5 while practicality obtained a score of 4.11 in the good category